Assessing effectiveness of heart rate variability biofeedback to mitigate mental health symptoms: a pilot study - Castro Ribeiro, Thais; Sobregrau Sangrà, Pau; García Pagès, Esther; Badiella, Llorenç; López-Barbeito, Beatriz; Aguiló, Sira; Aguiló, Jordi (Frontiers in Physiology, 2023)
Introduction: The increasing burden on mental health has become a worldwide concern especially due to its substantial negative social and economic impact. The implementation of prevention actions and psychological interventions are crucial to mitigate these consequences and evidence supporting its effectiveness would facilitate a more assertive response. Heart rate variability biofeedback (HRV-BF) has been proposed as a potential intervention to improve mental wellbeing through mechanisms in autonomic functioning. The aim of this study is to propose and evaluate the validity of an objective procedure to assess the effectiveness of a HRV-BF protocol in mitigating mental health symptoms in a sample of frontline HCWs who worked in the COVID-19 pandemic. Methods: A prospective experimental study applying a HRV-BF protocol was conducted with 21 frontline healthcare workers in 5 weekly sessions. For PRE-POST intervention comparisons, two different approaches were used to evaluate mental health status: applying (a) gold standard psychometric questionnaires, and (b) electrophysiological multiparametric models for chronic and acute stress assessment. Results: After HRV-BF intervention, psychometric questionnaires showed a reduction in mental health symptoms and stress perception. The electrophysiological multiparametric models also showed a reduction in chronic stress level while the acute stress model revealed similar PRE-POST levels. A significant reduction in respiratory rate, and an increase in some HRV parameters, such as SDNN, LFn and LF/HF ratio, were also observed after intervention. Conclusion: Our findings suggest that a 5-session HRV-biofeedback protocol is an effective intervention for reducing stress and other mental health symptoms among frontline healthcare workers who worked during the COVID-19 pandemic. The electrophysiological multiparametric models provide relevant information about the current mental health state, being useful for objectively evaluating the effectiveness of stress-reducing interventions. Further research could replicate the proposed procedure to confirm its feasibility for different samples and specific interventions.